Necropolitics and Slow Violence: Revisiting Migrants’ Access to Healthcare during the COVID-19 Pandemic in South Africa - Mutekwe , Paddington; Chiwarawara, Kenny (African Human Mobility Review, 2025)
Migrants constitute a vulnerable group of individuals. Such vulnerability is pronounced during times of crises such as a pandemic. South Africa recorded its first COVID-19 case on 5 March 2020, and the cases kept on surging, prompting the government to announce a nationwide lockdown on 23 March 2020. The COVID-19 lockdown engendered socioeconomic, protection, and health challenges to the entire population but with a unique effect on vulnerable groups such as foreign nationals. This paper examines the health challenges foreign nationals faced in South Africa during the COVID-19 pandemic. Theoretically, the paper uses Achille Mbembe’s notion of necropolitics to argue that the exclusion of migrants from accessing healthcare resulted in the manufacture of a population who lived at the margins of society, where living meant continually standing up to face death in their everyday lives (slow violence). Methodologically, the paper draws on a qualitative study conducted during the COVID-19 pandemic, where data were generated through in-depth interviews and document analysis. The paper’s key findings are that foreigners faced medical exclusion in accessing healthcare and COVID-19 vaccines, and they also faced a lack of information and language barriers, which negatively impacted their access to healthcare services. The paper concludes that these challenges stem from a lack of political will to adequately include foreigners in health initiatives. The insights of this paper may prove helpful in considering inclusive health initiatives.